City and Development: Business and Forestry Imaginary in Concepción, Chile - Carrasco Henríquez, Noelia Gabriela; Universidad de Concepción, Chile (Editorial Pontificia Universidad Javeriana, 2017)
The main forestry companies in Chile have their management hubs in the Biobío region. From there, they deploy programs and design actions that make evident the current convictions of the business world regarding the territory and its uses. We propose as an objective to examine the way in which the entrepreneurial imaginaries of the capitalist city are installed and expanded here, favoring an ideological and cultural motor of the current multinational capitalism. Based on an ethnographic methodology complemented with the data and scope of geography, we propose to describe this imaginary of the developed urban space, based on operational, political, and historical references. The results obtained reinforce the interpretation of the city transformations to the rhythm of the evolution of organized capitalism in the territory, due to the expansion of the forest industry.